SUBDUCTION HISTORY OF THE TETHYAN REGION DERIVED FROM SEISMIC TOMOGRAPHY AND TECTONIC RECONSTRUCTIONS - Hafkenscheid E.; Wortel M.J.R.; Spakman W. (My University, 2006)
In the mantle underneath the Tethyan suture zone, large volumes of positive velocity anomalies have been imaged by seismic tomography and interpreted as the present-day signature of subducted. Tethyan lithosphere. We investigate the Mesozoic-Cenozoic subduction history of the region by integrating independent information from mantle tomography and tectonic reconstructions. Three different subduction scenarios for the Tethyan oceanic lithosphere, representative for the available tectonic reconstructions, are used to predict the present thermally anomalous volumes associated with the lithospheric surface subducted since the late Mesozoic. Next, these predicted thermal volumes and their expected positions are compared to the relevant anomalous volumes derived from seismic tomographic images. In this analysis we include, among others, the possible effects of ridge subduction and slab detachment after the Cenozoic continental collisions, absolute plate motion, and slab thickening in the mantle. Our preferred subduction model comprises the opening of large back-arc oceanic basins within the Eurasian margin. The model points to slab thickening by a factor of 3 in the mantle, in which case the estimated volumes allow for active oceanic spreading (~1-2.5 cm/yr) in the Tethyan lithosphere during convergence. Our results further indicate the occurrence of early Oligocene slab detachment underneath the northern Zagros suture zone, followed by both westward and eastward propagation of the slab tear and diachronous Eocene to Miocene slab detachment below the eastern to western Himalayas. Free sinking rates of the detached material of ~2 cm/yr in the lower mantle provide the best fit between the tomographic mantle structure and our Tethyan subduction model. Copyright 2006 by the American Geophysical Union.
Keywords: Miocene; Oligocene; Eocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен